Digestible methionine plus cystine requirements of ISA Label broilers reared in free-range system - Nagib Nascimento, Daphinne Cardoso; Sakomura, Nilva Kazue [UNESP]; de Siqueira, Jefferson Costa; Freitas Pinheiro, Sandra Regina; Kochenborger Fernandes, Joao Batista [UNESP]; Furlan, Renato Luis [UNESP] (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2009)
Three assays were carried out to determine the digestible methionine+cystine (Met+Cys) requirement for ISA Label broilers from both sexes. The birds were reared in free range system on starting phase (1 to 28 days), growing phase (28 to 56 days) and finishing phase (56 to 84 days). Four hundred and eighty birds were distributed into 24 pens, each one composed of shelter (3.13 m(2)) and pasture (72.87 m(2)). The experimental design was completely randomized with eight treatments as factorial arrangement (four Met+Cys levels and two sexes) with three replicates of 20 birds. The digestible Met+Cys levels were 0.532; 0.652; 0.772; 0.892% for starting phase; 0.515; 0.635; 0.755; 0.875% for growing phase and 0.469; 0.589; 0.709; 0.829% for finishing phase. The analyzed parameters were performance, carcass yield, body protein and fat deposition, weight and protein concentration in feathers. In the starting phase, the digestible Met+Cys level estimated for males was 0.765 and 0.803% for females, corresponding to 0.252 and 0.268% of Met+Cys/Mcal of ME, respectively. For the growing phase, the digestible Met+Cys level estimated was 0.716% for both sexes, corresponding to 0.235% of Met+Cys/Mcal of ME. For the finishing phase, the Met+Cys levels were 0.756 and 0.597% for males and females, corresponding to 0.244 and 0.193% of Met+Cys/Mcal of ME respectively.
Keywords: Broilers; Naked-neck birds; sulphurous amino acids